Characterization of alkali silica reaction gels using Raman spectroscopy. (February 2017) - Balachandran, C.; Muñoz, J.F.; Arnold, T.
Abstract: The ability of Raman spectroscopy to characterize amorphous materials makes this technique ideal to study alkali silica reaction (ASR) gels. The structure of several synthetic ASR gels was thoroughly characterized using Raman Spectroscopy. The results were validated with additional techniques such as Fourier transmission infrared spectroscopy, X-ray powder diffraction and thermogravimetric analysis. The Raman spectra were found to have two broad bands in the 800 to 1200 cm − 1 range and the 400 to 700 cm − 1 range indicating the amorphous nature of the gel. Important information regarding the silicate polymerization was deduced from both of these spectral regions. An increase in alkali content of the gels caused a depolymerization in the silicate framework which manifested in the Raman spectra as a gradual shift of predominant peaks in both regions. The trends in silicate depolymerization were in agreement with results from a NMR spectroscopy study on similar synthetic ASR gels.